Challenges and recusals of judges and arbitrators in international courts and tribunals - Giorgetti, Chiara (Brill Nijhoff, 2015)
"Challenges and Recusal of Judges and Arbitrators in International Courts and Tribunals" provides an in-depth analysis of a fundamental control mechanism of international dispute resolution in the context of some of the main international courts and tribunals. The book also assesses specific grounds and standards for challenging judges and arbitrators, and includes both regional and personal perspectives.